PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN CANVA TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN LITERASI DIGITAL SISWA KELAS X PADA MATA PELAJARAN BIOLOGI DI SMA NEGERI 1 TANJUNG BINTANG - Nazira, Aydellia; Kesumawardani, Aryani Dwi; Sada, Heru Juabdin; Oktafiani, Raicha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking skills and digital literacy are essential competencies for students to face the challenges of the 21st century. These skills enable learners to analyze information effectively, solve complex problems, and use technology responsibly in various contexts. However, in many classrooms, these competencies are often underdeveloped due to the predominance of conventional, teacher-centered learning methods that do not actively engage students in problem-solving or technology integration. This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by Canva on the critical thinking skills and digital literacy of tenth-grade students in Biology at SMA Negeri 1 Tanjung Bintang. The research employed a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design, to compare the performance of students in two learning conditions. The population consisted of 359 students, with a sample of 36 students in class X.1 as the experimental group using PBL assisted by Canva, and 36 students in class X.2 as the control group using the Discovery Learning model. Instruments included an essay-based critical thinking skills test and a digital literacy questionnaire developed based on established indicators. Both instruments underwent validity and reliability testing prior to use. Data were analyzed using the Independent T-test with SPSS version 25 after testing for normality and homogeneity. The results showed a significant effect of the PBL model assisted by Canva on both critical thinking skills and digital literacy, indicated by significance values of less than 0.05 for both variables. Therefore, the PBL model assisted by Canva is proven effective in enhancing students’ higher-order thinking and digital competencies, making it a recommended approach for Biology learning and potentially for other science subjects in secondary education. Keywords: Problem Based Learning, Critical Thingking, Digital Literacy